Public Sector Reforms and Service Delivery in Kenya: A Critical Literature Review - Eliud Owalo; Evans Aosa (DBA Africa Management Review, 2026)
This paper critically examines the relationship between public sector reforms and service delivery. A critical literature review was employed to identify, synthesize and classify publications relating to public sector reforms across different contexts with emphasis on the public sector in Kenya. This was followed by a synthesis of the literature for purposes of identifying research gaps in respect to the efficacy of public sector reforms on service delivery. The findings reveal that while Kenya has made substantial progress in implementing various public sector reforms anchored on New Public Management framework, mixed performance results on service delivery still prevail. Key barriers to successful reforms were identified to include corruption, political interference, and institutional inefficiency. The findings contribute to the ongoing debate among scholars regarding the relevance and efficacy of public sector reforms based on the New Public Management orthodoxy. This article provides practical insights on the challenges of public sector reforms and the need for context specific policy interventions required to enhance service delivery. Key among the recommendations made in this paper to enhance service delivery in the public sector include; adoption of digitalization, decentralization, and strengthening institutional and corporate governance frameworks.